Climate change impacts on high rise buildings - Pan, Xiao (2015)
Global climate change has been a major concern for the built environment nowadays. On the other hand, currently, high rise buildings have become the major construction trend due to land constraint in Singapore. Hence, the climate change impacts especially due to temperature, rainfall and wind on high rise buildings has become a serious issue. This report focuses on literature review on works done in other countries to analysis the condition of Singapore. Climate change mitigation and adaption are also made in order to strengthen the climate resilience of high rise buildings and therefore a more sustainable built environment in the future.